2013
DOI: 10.1097/prs.0b013e31829589db
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Extensor Lag and Range of Motion following Free Vascularized Joint Transfer to the Proximal Interphalangeal Joint

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Extension lag is commonly reported and is considered by some to be unavoidable with both vascularized and nonvascularized digital joint transfer. 20,21 There is a natural extension lag of 16° in the second toe PIP joint, while reported postoperative extension lag ranges between 17.1 and 42.5° in vascularized whole toe joint transfers. 20,23 Multiple methods have been described to reinforce the central slip attachment and mitigate attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…Extension lag is commonly reported and is considered by some to be unavoidable with both vascularized and nonvascularized digital joint transfer. 20,21 There is a natural extension lag of 16° in the second toe PIP joint, while reported postoperative extension lag ranges between 17.1 and 42.5° in vascularized whole toe joint transfers. 20,23 Multiple methods have been described to reinforce the central slip attachment and mitigate attenuation.…”
Section: Discussionmentioning
confidence: 99%
“…A cadaveric study of toe PIPJs performed by Lam et al 10 revealed 2 distinct extensor tendon mechanisms. The more common of the two, coined “type 1” toes, are those with an attenuated central slip similar to a thin aponeurosis that lacks a distinct insertion onto the middle phalangeal base.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to optimize functional outcomes, Lam et al 10 developed an algorithm (later refined by Loh et al 3 ) focused on dynamic assessment of 3 factors: the donor toe central slip, recipient finger lateral bands, and lumbrical system. Depending on the integrity of the central slip of the donor toe and lateral bands at the recipient PIPJ, the extensor mechanism is either centralized, reconstructed, or repaired directly to the donor extensor tendon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MPJ and PIPJ are responsible for most of a digit's ROM, whereas the point of DIPJ preservation is typically to preserve length, and therefore motion is not as significant a concern. 12 Hierner and Berger 6,20,21 proved that there was no significant difference in results between toe joint and heterodigit joint transplantation. Based on our experience, we can classify the heterotopic joint transfer as same level joint transfer, distal to proximal joint transfer, and proximal to distal joint transfer.…”
Section: The Position Of Donor and Recipient Jointmentioning
confidence: 95%